Analisis Miskonsepsi Dalam Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) Pada Guru Sekolah Dasar Di Kecamatan Kayen - Lizza, Fida Syarofiyatul; Purnamasari, Iin; Ardiyanto, Asep (CV. Supernova Office Stationary and Printing, 2024)
The research context that drives this research is the finding of misconceptions made by teachers in PJOK learning in elementary schools. PJOK learning in elementary school generally experiences a lot of obstacles, one of which is the learning model applied by many undisciplined elementary school teachers. Applied by many undisciplined elementary school teachers. The problem in this study is the factors that influence the occurrence of misconceptions and how patterns that allow misconceptions to occur in PJOK teachers. the purpose of this study is to analyze the problem factors why misconceptions occur in PJOK learning and analyze how the pattern of misconceptions in PJOK learning. This type of research uses qualitative methods. The research subjects in this study were principals and PJOK teachers in Kayen District. The sample used in this study amounted to 38 informants. Data collection techniques were carried out using observation, interviews, questionnaires and documentation. The results showed that the factors that influence misconceptions in PJOK learning based on the results of data analysis, are activities carried out, teaching concepts by teachers, and the ability and learning methods applied by teachers. Other factors that cause misconceptions experienced by students arise from within students and outside students. Factors from outside students include a lack of understanding of the new curriculum, lack of use of varied and interactive learning methods, and lack of understanding of student characteristics and stages of development.